(untitled) (Palíndromo, 2024)
The objective of the text is to present a possibility of analysis of landscape painting from the Hudson River School, and particularly of Albert Bierstadt’s work, through an examination of ontological and socio-historical factors. The aim is to develop two points. First, to show how the naturalistic ontology organizes the hegemonic way of classifying these paintings; second, to restore the plausible modes of representation prevalent during the period of the paintings’ creation beyond the naturalistic criteria dominant today. It is concluded, with the aid of instruments for analyzing the environmental history of art, that the pursuit of “styles of attention” practiced in the works consisted of attempts by painters like Bierstadt to capture a natural world on the verge of destruction.